Vitamin E and curcumin intervention on lipid-peroxidation and antioxidant defense system - Amani, Alireza; Somchit, Muhammad Nazrul; Konting, Mohd Majid; Kok, Lian Yee (Marsland Press, 2010)
The generation of free radical species may represent the negative aspect of exercise. There are a lot of data which have been shown an association between exercise and the increased free radical formation. Living cellular damage may lead human towards hasty aging and variant cancers. It is widely agreed that with increasing consumption of fruits and vegetables, decreased intake of unsaturated fat and moderate exercise will enhance fitness and improved cardiovascular health of the population in most of the developed and near-developed countries. Vitamin E and Curcumin have been known as a strong Antioxidant for prevent of the lipid peroxidation and improve the antioxidant defense system. Curcumin is a phenolic compound presented as a strong anti-oxidative, anti-inflammatory and anti-septic property, widely used in Indian medicine and culinary traditions. Recent investigation has shown that curcumin prevents lipid peroxidation and DNA strand breakage. This review have been shown the effect of the curcumin and vitamin E supplement on the lippid peroxidation and antioxidant defense system specify during the exercise.